The role of brain derived neurotrophic factor in central nervous system - Li, Yiyi; Li, Fang; Qin, Dongdong; Chen, Hongyu; Wang, Jianhao; Wang, Jiabei; Song, Shafei; Wang, Chao; Wang, Yamei; Liu, Songyan; Gao, Dandan; Wang, Zhi-Hao (Frontiers in Aging Neuroscience, 2022)
Brain derived neurotrophic factor (BDNF) has multiple biological functions which are mediated by the activation of two receptors, tropomyosin receptor kinase B (TrkB) receptor and the p75 neurotrophin receptor, involving in physiological and pathological processes throughout life. The diverse presence and activity of BDNF indicate its potential role in the pathogenesis, progression and treatment of both neurological and psychiatric disorders. This review is to provide a comprehensive assessment of the current knowledge and future directions in BDNF-associated research in the central nervous system (CNS), with an emphasis on the physiological and pathological functions of BDNF as well as its potential treatment effects in CNS diseases, including depression, Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, multiple sclerosis, and cerebral ischemic stroke.